The Role of Government, Islamic Banks, And Waqf in Inclusive Economic Development in Indonesia - Musyaffa, Ahmad Naufal; Luthfi, Agus; Amijaya, Rachmania Nurul Fitri (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2025)
This study examines the relationship between government spending variables, Islamic commercial bank financing, and waqf, focusing on the inclusiveness of economic development, using a quantitative approach to explanatory research. A panel data regression analysis model is used to test the hypotheses. The results of the analysis partially explain that government spending and Islamic commercial bank financing have a significant positive effect on the inclusiveness of economic development. Meanwhile, the waqf variable does not affect the inclusiveness of economic development. This study uses Ibn Khaldun’s hikkamiyah theory to explain economic development. By improving the quality of institutions, such as the government and financial sector, and applying fair principles in conducting economic development in Indonesia, inclusive economic development becomes more realistic.